PENGARUH PROGRAM PELATIHAN DAN PENGEMBANGAN TERHADAP KINERJA KARYAWAN PADA PT. BANK CENTRAL ASIA, TBK (Studi Pada Frontliner Bakti BCA KCU Banjarmasin) - Elaine Tjeng; Laila Refiana Said; Wimby Wandary (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
This study aims to identify and analyze the effect of the training program ( X1 ) and program development ( X2 ) as independent variables either partially or simultaneously on employee performance ( Y ) as the dependent variable in the PT . Bank Central Asia Tbk ( BCA KCU Banjarmasin ) . Methods This study used a questionnaire with 65 Frontliner Bakti BCA KCU Banjarmasin as the sample . Measurement variables using Likert Scale technique with 6 levels of approval . To determine the effect of variables X1 and X2 to Y used multiple linear regression statistical techniques and fatherly significance testing using the F test and t-test using SPSS . The results of this study concluded that the partial of the two independent variables , only the training programs that have a significant influence on employee performance . No significant effect of the two independent variables simultaneously to variable employee performance